Fuzzy Comprehensive Evaluation of Mixed Reality Seismic Retrofitting Training System - Zhansheng Liu; Jie Xue (Buildings, 2022)
Due to the complexity of the construction environment and retrofitting methods, it is difficult to achieve the expected retrofitting effect. Therefore, effective seismic retrofitting training is a necessary way to ensure retrofitting workers acquire enough professional knowledge, skills and safe behaviors, which are critical to retrofitting. Mixed reality has huge potential in construction training. This paper conducts a fuzzy comprehensive evaluation of the MR seismic retrofitting training system to research the potential of MR in training. The purpose of this research was to provide scientific guidance and reference for the development, improvement and selection of MR training systems in the future. In this research, the evaluation indicators of the MR training system were firstly analyzed. Next, the weight of each evaluation indicator was calculated by the judgment matrix. Then, the evaluation model was established based on the qualitative–quantitative transformation principle of indicators. Finally, the results of the MR seismic retrofitting training system are obtained by combining the evaluation model with the membership matrix. The evaluation result of the training system in this paper is excellent.